Apex - USM Gets Apex Status. - The Star, Online (2008)
PUTRAJAYA: Universiti Sains Malaysia (USM) has been granted apex status. With it, USM can expect hundreds of millions of ringgit in additional funding to transform it into Malaysia's first world-class university. Higher Education Minister Datuk Seri Mohamed Khaled Nordin said that quantitative and qualitative criteria were used to select USM under the accelerated programme for excellence (apex).